Paul Hindemith: „Übungsbuch für elementare Musiktheorie“ - Franz Comploi (Musica Docta, 2017)
The article is a critical reflection on the contents and relevance of Paul Hindemith’s 1946b handbook Elementary Training for Musicians, republished in German in 1975 under the title Übungsbuch für elementare Musiktheorie. The purpose of the article is to contribute to the debate, started many years ago, on the need for a solid music training addressed to all citizens.